Forest Cover Change Detection and Water Yield Relationship in Semenyih and Langat Watershed Using Remote Sensing Technique - Ismail, Mohd Hasmadi (2000)
The water supply and its quality would be a worrying situation in the region where there is rapid urbanization, industrial and agriculture development. Lack of proper planning in land use especially in the forest watersheds may lead to the problem of insufficient water supply to the nation. One of the major water supply areas facing problem of water shortage is the Hulu Langat watershed, where the critical recession of water resources at the end of 1990' s has been the main drawback of environmental changes in the area. The general objective of this study was to develop a technique of Landsat TM modeling that provides spatial information on the current land use trend in Hulu Langat catchment and its vicinity using remote sensing technology. The specific objectives were as follows: (1) to identify and quantify forest cover depletion surrounding the two dams using three different years of satellite data (1993, 1996 and 1998); (2) to determine the causes and factors influencing water yield in Semenyih and Langat dam and; (3) to map the water turbidity in Langat and Semenyih dam by remote sensing technique with 30m spatial resolution. Based on the comparison between two multi-temporal imagery of 1993 and 1998, primary forest cover area decreased from 9,316 to 6,818 ha, agriculture/ secondary forest area increased from 1,391 to 1,670 ha, urban/clear land increased from 265 ha to 427 ha, and water bodies decreased from 489 ha to 430 ha. The annual percentage of deforestation in the study area was about 0.054 percent per ha per year and the total deforestation was 2,497.5 ha from 1993 to 1998.